Removal of Chemical Oxygen Demand, Total Organic Carbon and Color from Textile Industry Wastewater by Using Phanerochaete chrysosporium (ME446) - Yildirim, Numan; Erguven, Gokhan Onder; Çelik, Aytekin (My University, 2021)
Wastewater discharge from textile industries concern environmental risks. Superiority of microbial methods over other high cost combined methods includes conversion of persistent organic materials to non-toxic last materials, sustainability, low cost, and comfortable. Textile wastewaters can have opposite effects on the quality of water in total organic carbon (TOC) and Chemical oxygen demand (COD). Agitation cultures can reach the surface area of the dyes, whereas a static cannot do. Biotreatment of textile wastewater from the dyeing process using white-rot fungus Phanerochaete chrysosporium (P.C) was investigated in agitated and static culture conditions. Dye is the major pollutant component in this wastewater includes some different organic pollutants. The treatment mediums containing distilled water in 1:10 ratio of wastewater were compared for treatment efficiency of P.C. Especially in agitated conditions at 27 oC and 150 rpm, it was achieved a successful treatment results. Under these conditions, a 48h long treatment reduced by 91,46 % of the original COD (from 1484 mg l-1) and by 94,92% the TOC (initial was 723.66 mg l-1). Moreover, treatment reduced color by 86,28 % from 3.550 A540 to 0.487 A540 at the end of the study. The decolorization properties of P.C obtained high performance and we determined P.C showed up to effective removal rate for COD and TOC within 48 hours. We suggest that these fungus pellets of P.C can reach the decolorization and can be a useful tool for bioremediation of textile dye wastewater within a short time period.
Keywords: Bioremediation; COD; Textile wastewater; TOC